Pandemi Covid-19 terhadap Kondisi Psikologis Petugas Kesehatan - Lilik Wijayati; Djazuly Chalidyanto; Budhi Setianto (Jurnal Keperawatan Silampari, 2021)
This study aims to examine the effect of the COVID-19 pandemic on the psychological condition of health workers. The research design used is a systematic search on several databases, including DOAJ, Sage, Proquest, Medline, Google Scholar, Science Direct, from February to June 2020. There is Rational pre-clinical evidence regarding mental or psychological health risks from several articles as a result of Covid-19. Feelings of anxiety, stress, depression or fear, and even panic due to Covid-19 trigger increased psychological or mental health risks faced by health workers so that therapy or group or individual activities need to be carried out. In conclusion, there is reasonable pre-clinical evidence regarding the mental or psychological health risks due to corona. Anxiety, stress or depression or fear, and even panic due to this corona case trigger increased psychological or mental health risks faced by health workers so that therapy or group or individual activities need to be applied. Keywords: Covid-19, Pandemic, Health Services, Health Officers, Psychological